Hydration behavior study of imidazolium based ILs in water - Lal, B. (Trans Tech Publications Ltd, 2014)
These ILs were chosen to provide an understanding of the influence of the cation alkyl chain length, and the anion influence on the volumetric properties. Densities for aqueous solutions of ionic liquids having 1-butyl-3-methylimidazolium as cation and chloride, bromide, iodide and acetate as anions were accurately measured at various concentrations and temperature, (288.15, 293.15, 298.15, 303.15 and 308.15) K. The results have been discussed in terms of hydrophobic hydration, hydrophobic interactions, and water structural changes in aqueous medium. The data were used in evaluating thermodynamic properties as apparent molar volumes, and apparent molar expansions. Apparent molar volumes were found to increase with temperature. Â© 2014 Trans Tech Publications, Switzerland.